Pro-environmental behaviours and protection motivation theory: a case of two universities in Bandung, Indonesia - Annisa Ritka May; Anindrya Nastiti (Jurnal Teknik Lingkungan, 2022)
Maladaptive behaviour towards the environment can threaten environmental conditions and this requires a more in-depth analysis. Students as part of the younger generation have the responsibility as educators, planners, and policymakers on environmental issues for a sustainable future so that research on university students’ pro-environmental behaviour is needed. This study adopted a developed causal model of pro-environmental behaviour based on Protection Motivation Theory (PMT) in a sample of 363 Indonesian university students. This theory is expected to identify barriers and impulses in carrying out pro-environmental behaviour. Based on the results, environmental attitude, self-efficacy, response costs, intrinsic and extrinsic rewards from maladaptive behaviour to the environment, and perceived severity of respondents' have a direct and significant effect on pro-environmental behaviour. In addition, perceived vulnerability has an indirect effect on pro-environmental behaviour through the level of perceived severity. Improving pro-environmental behaviour for students could be focused on environmental attitude and self-efficacy through environmental protection based on a tested causal model